THE AUTHENTICITY OF MUTTAFAQ HADITHS BY IBN KHUZAIMAH AND AL-HĀKIM: A REVIEW - Amaliyah, Nailah; Redha, Inaya Hartina; Hermanto, Muhammad Fadli; Putra, Ferangga Wimbodyo Sunarto; Muhid, Muhid (Nabawi: Journal of Hadith Studies, 2023)
The muttafaq hadith, apart from Ṣaḥīḥ Bukhari-Muslim, is not widely known, even though there are other Sahih books besides those two. Among the Sahih books are Ṣaḥīḥ Ibn Khuzaimah and Mustadrak al-Hakim. While the authenticity of the muttafaq 'alaih (The hadith of Bukhari-Muslim) is clear and accepted by all Muslims, the same cannot be said for the authenticity of muttafaq hadith outside of Bukhari-Muslim. There is an assumption that the similarity in the chain of narration (sanad) of muttafaq hadith narrated by Imams apart from Bukhari-Muslim does not always indicate the authenticity of the hadith. To test this assumption, this research uses four samples of muttafaq hadith on the topic of "Friday bathing" from Sahih Ibn Khuzaimah and Mustadrak al-Hakim as the primary data. Data analysis reveals that the similarity in the sanad of muttafaq hadith is not an indicator of the authenticity of the sanad, but the similarity in the text (matan) of muttafaq hadith provides an indication of its authenticity. These findings demonstrate that the higher standard of hadith authenticity set by Imam Ibn Khuzaimah compared to Imam al-Hakim does not guarantee that their muttafaq hadith meets the criteria of hadith authenticity. This research provides new insights into the evaluation of the authenticity of muttafaq hadith in hadith studies. [Hadis muttafaq selain Ṣaḥīḥ Bukhari-Muslim, belum begitu dikenal, padahal kitab ṣaḥīḥ tidak hanya dua itu. Di antara kitab Ṣaḥīḥ adalah Ṣaḥīḥ Ibn Khuzaimah dan Mustadrak Ḥākim. Jika ke-saḥīḥ-an hadis muttafaq ‘alaih (Bukhari-Muslim) sudah jelas dan diterima semua muslim, tidak demikian dengan ke-saḥīḥ-an hadis muttafaq selain Bukhari Muslim. Terdapat asumsi bahwa kesamaan dalam sanad hadis muttafaq antar Imam selain Bukhari-Muslim tidak selalu menunjukkan ke-saḥīḥ-an hadis. Untuk menguji asumsi tersebut, penelitian ini menggunakan 4 sampel hadis muttafaq dengan topik “mandi hari Jumat” dari kitab mereka sebagai data utama. Analisis data menunjukkan bahwa kesamaan dalam sanad hadis muttafaq tidak menjadi indikator ke-saḥīḥ-an sanad, tetapi kemiripan dalam matan hadis muttafaq memberikan indikasi ke-saḥīḥ-an matan. Temuan ini menunjukkan bahwa standar ke-saḥīḥ-an hadis Imam Ibn Khuzaimah yang lebih tinggi daripada Imam al-Hakim, tidak mampu memberi kepastian bahwa hadis muttafaq keduanya memenuhi syarat ke-saḥīḥ-an sanad dan matan. Hasil penelitian ini memberikan pemahaman baru tentang penilaian ke-saḥīḥ-an hadis muttafaq dalam kajian hadis.]